Species and Termite Attack Intensity on Pine Trees in Nagari Talang Babungo, Solok District, West Sumatra Province - Desyanti Desyanti; Fauzan Fauzan; Zulhilda Yenti (Jurnal Proteksi Tanaman, 2023)
Termites are classified as insects that destroy trees and other organic materials containing cellulose, including pine trees. The species and attack intensity of termites on pine trees in the protected forest of Nagari Talang Babungo, Solok District, West Sumatra Province, is unknown. This study aimed to determine the type and intensity of termite attacks on pine trees in the protected forest of Nagari Talang Babungo, Solok District, West Sumatra Province. This research was conducted by survey method with direct observation and graveyard test techniques. Based on the results, it was found that around 7.8% of pine trees in the Nagari Talang Babungo Protection Forest, Hiliran Gumanti sub-district, Solok Regency, West Sumatra Province, were attacked by termites Nusitutermes sp, which was indicated by the presence of termite galleries on the trunks and bases of the stems. The intensity of the termite attack was relatively low, with a percentage of lose weight by using graveyard test was 17.7%.